Análisis de mercado para la importación de cuchillos especiales de chef desde China hacia el Ecuador, para comercializarlos a los alumnos de gastronomía de la ciudad de Quito - Enríquez Escobar, Rommel Alexey (2014)
This paperwork has as main objective to analyze the feasibility of importing special chef knives from China to Ecuador, to commercialize them to students of gastronomy in Quito and, in this analysis, identify the main variables such as: Transportation, Commercial Restrictions or Covenants between Ecuador and China affecting the importation of the good in question; tariff advantages or disadvantages. The analysis has also enabled the theoretical framework proposed, link with the practical reality and finally implement an appropriate marketing strategy for selling the property wanted to import, which will reach the expected level of sales, under an analysis of the existing demand, making this project profitable from a financial point of view…